Skrining Penyakit Tidak Menular dan Kanker Leher Rahim pada Masyarakat di Kota Luwuk Kabupaten Banggai: Screening for Non-Communicable Diseases and Cervical Cancer in the Community in Luwuk City, Banggai Regency - Wijianto Wijianto; Nurarifah Nurarifah; Sukmawati Sukmawati; Djadid Subchan; Dian Kurniasari Yuwono; Sri Murniawati Hasan; Hana Yulianti Muhammad; Dg. Mangemba; Nitro Galenso (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Non-Communicable Diseases (NCDs) are diseases that are not transmitted to other people through any form of contact. Examples of NCDs include stroke, coronary heart disease, cancer, diabetes mellitus, hypertension, and conditions resulting from accidents and violence. In Banggai Regency, the number of people with NCDs continues to increase, with 5.2% having hypertension and 8.5% having diabetes mellitus in 2021. NCDs can be detected through early detection by measuring blood pressure, cholesterol levels, blood sugar, and body mass index (BMI). The aim of this activity is to screen for NCDs and cervical cancer. The participants of this activity are 22 women from the Ministry of Religious Affairs Women's Association in Banggai Regency. The activity was conducted in October 2022 at the campus of the D3 Nursing Study Program in Luwuk. The examination method used rapid tests to measure cholesterol and blood sugar levels, while blood pressure was measured using a digital sphygmomanometer, and anthropometric measurements were taken to obtain BMI data. IVA tests were also conducted to detect cervical cancer. The results of the examination showed that 63.6% of the participants were at risk of pre-hypertension, 12.7% were at risk of hypercholesterolemia, and 31.8% were at risk of diabetes mellitus. The BMI measurements showed that 59.1% were in the obesity category, and 72.7% had an obese waist circumference. The IVA tests did not detect any risk of cervical cancer. NCD screening through routine health check-ups should be done periodically to detect NCD risks as early as possible.